2022
DOI: 10.5802/crchim.206
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of amino-functionalized carbon quantum dots-decorated hydroxyapatite as drug delivery agent

Abstract: Hydroxyapatite (HAp) was combined with amino-functionalized carbon quantum dots (CQDs) to enhance the optical and surface area properties of HAp. The loading of aminofunctionalized CQDs could enhance the luminescence of HAp and its UV-Vis absorbance. Additionally, surface area of HAp could be increased from 84.16 to 129.94 m 2 /g by loading aminofunctionalized CQDs. The drug release experiment was conducted using acetaminophen. The release happened slowly for amino-functionalized CQDs/HAp, with full release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, the surface area of HAP can increase from 84.16 m 2 g −1 to 129.94 m 2 g −1 , which is beneficial for drug loading. 89 The study on the synthesis of Mg-HAP samples using the reflux condensation method found that as the concentration of Mg increased, the recombination of charge carriers was blocked, and the photoluminescence intensity increased. 90 The self-luminescent property of Mg-HAP particles, which is because of their surface plasmon, can be used in imaging and drug delivery applications.…”
Section: Preparation Of Hap-based Carriersmentioning
confidence: 99%
“…In addition, the surface area of HAP can increase from 84.16 m 2 g −1 to 129.94 m 2 g −1 , which is beneficial for drug loading. 89 The study on the synthesis of Mg-HAP samples using the reflux condensation method found that as the concentration of Mg increased, the recombination of charge carriers was blocked, and the photoluminescence intensity increased. 90 The self-luminescent property of Mg-HAP particles, which is because of their surface plasmon, can be used in imaging and drug delivery applications.…”
Section: Preparation Of Hap-based Carriersmentioning
confidence: 99%